3D porous polymers for selective removal of CO2 and H2 storage: experimental and computational studies - Al-Bukhari, Muath S.; Abdulazeez, Ismail; Abdelnaby, Mahmoud M.; Aljundi, Isam H.; Al Hamouz, Othman Charles S. (Frontiers in Chemistry, 2023)
In this article, newly designed 3D porous polymers with tuned porosity were synthesized by the polycondensation of Tetrakis(4-aminophenyl)methane with pyrrole to form M1 polymer, and with phenazine to form M2. The polymerization reaction used p-Formaldehyde as a linker and nitric acid as a catalyst. The newly designed 3D porous polymers showed permanent porosity with a BET surface area of 575 m 2 /g for M1 and 389 m 2 /g for M2. The structure and thermal stability were investigated by solid 13 C-NMR, FT-IR, and TGA. The performance of the synthesized polymers toward CO2 and H2 was evaluated, demonstrating adsorption capacities of 1.85 mmol/g and 2.10 mmol/g for CO2 by M1 and M2, respectively. The importance of the synthesized polymers lies in their selectivity for CO2 capture with CO2/N2 selectivity of 43 and 51 for M1 and M2, respectively. M1 and M2 polymers showed their capability for hydrogen storage with a capacity of 66 cm 3 /g (0.6 wt.%) and 87 cm 3 /g (0.8 wt.%), respectively at 1 bar and 77 K. Molecular dynamics simulations using the Grand Canonical Monte Carlo (GCMC) method revealed the presence of considerable microporosity on M2, making it highly selective to CO2. The exceptional removal capabilities combined with the high thermal stability and microporosity enables M2 to be a potential material for flue gas purification, and for hydrogen storage.